ANALISIS PELAKSANAAN KURIKULUM 2013 DITINJAU DARI STANDAR PENILAIAN DALAM PEMBELAJARAN MATEMATIKA KELAS VIII DI SMP NEGERI 18 PADANG - Sherly Sherly (Horizon, 2021)
The purpose of this study is to describe and analyze the assessment mechanisms and procedures in accordance with 2013 curriculum rules. This research is a qualitative descriptive study. Subjects in this study were mathematics teachers in class VIII SMP Negeri 18 Padang, amounting to two teachers. The instruments used in this study include documentation, observation, and interviews. Data analysis techniques include data reduction, presentation, data verification, and data triangulation. The results of this study indicate (a) in terms of the assessment mechanism of eighth grade mathematics teachers at SMPN 18 Padang not yet perfect in implementing the assessment mechanism stipulated in Permendikbud No. 23 of 2016 The imperfect indicators are 1) carry out attitude assessments with various assess,emt techniques, 2) carry out skills assessments with varios asessment techiques. (b) in terms of the assessment procedure for eighth grade mathematics teachers at SMPN 18 Padang, it is also perfect to carry out the assessment procedures stipulated in Ministry of Education and Culture Regulation No. 23 of 2016. As for the imperfect indicators, namely 1) determining the purpose of the assessment, 2) make analysis of instrument quality, 3) processing, analyzing, and interpreting the assessment, 4) reprting the reults of the assessment, 5) utilizing the results of the asessment report.